Metastatic Cryptococcosis as a Manifestation of Immune Reconstitution Inflammatory Syndrome in a Patient With COVID-19 Infection: na - Jilani, Abdulhakim; Alshmandi, Mohamed; Kiernan, Julia (Scripta Medica, 2024)
Disseminated cryptococcosis is an infrequent fungal illness primarily observed in immunocompromised individuals, particularly among those with human immunodeficiency virus (HIV). In this report, a case where the initiation of antiretroviral therapy revealed a previously hidden Cryptococcus infection in an HIV-positive male who also had COVID-19 is presented. A 30-year-old male with a medical history of HIV sought medical attention at the Emergency Department due to the presence of a widespread, non-itchy skin rash along with severe difficulty breathing. Diagnosis of unmasking immune reconstitution inflammatory syndrome (IRIS) associated with disseminated cryptococcosis, all while testing positive for COVID-19 was made based on clinical presentation and performed analyses. COVID-19 management guidelines were strictly adhered to and treatment included the administration of steroids, amphotericin B and fluconazole. Additionally, empirical coverage for Pneumocystis carinii pneumonia (PCP) was initiated. Regrettably, the patient's clinical condition deteriorated in the following days, ultimately resulting in his passing. The ongoing pandemic has understandably prioritised the diagnosis of COVID-19 by healthcare providers, sometimes overshadowing the exploration of alternative diagnoses. It is crucial to maintain a heightened clinical suspicion for opportunistic infections, especially among immunocompromised individuals, particularly those with HIV.
Keywords: COVID-19; HIV; Kriptokokoza